Calibrating ratings of perceived fatigue relative to objective measures of localised muscle fatigue using a feedback-based familiarisation protocol. (15th June 2021) - M. Abdel-Malek, Daniel; Foley, Ryan C. A.; Wakeely, Fahima; Graham, Jeffrey D.; Delfa, Nicholas J. La
Abstract: Localized muscle fatigue (LMF) manifests as a reduction in muscle force generating capacity, an increase in electromyography signal amplitude and a decrease in mean power frequency (MnPF). Estimates of LMF can also be obtained subjectively through ratings of perceived fatigue (RPF); however, the provision of RPF scale familiarisation is inconsistent within the literature. The purpose of this study was to explore the effect of an RPF familiarisation session on the accuracy of RPF, relative to objective measures of fatigue, during a LMF protocol. Twenty participants performed intermittent isometric elbow flexion efforts to fatigue. Following each 5-minute cycle, RPF ratings were provided using a visual analog scale, and an MVC was obtained. On day 2, the 'feedback' group received visual feedback pertaining to their reduction in MVC, immediately following their RPF input, while the control group received no feedback. On day 3 (retention), RMSE was 72% lower between RPF and MVC, and 69% lower between RPF and MnPF for the feedback group after the familiarisation period. Findings support the inclusion of a familiarisation session to improve RPF as a surrogate measure for traditional objective measures of LMF.